FoxO1-zDHHC4-CD36 S-Acylation Axis Drives Metabolic Dysfunction in Diabetes - Dennis, Kaitlyn M. J. H.; Gopal, Keshav; Montes Aparicio, Claudia N.; Zhang, Jiashuo Aaron; Castro-Guarda, Marcos; Nicol, Thomas; Devereux, Riona M.; Carter, Ryan D.; Azizi, Saara-Anne; Lan, Tong; Purnama, Ujang; Carr, Carolyn A.; et al. (LIPPINCOTT WILLIAMS & WILKINS, 2025)
BACKGROUND: The fatty acid (FA) transporter CD36 (FA translocase/cluster of differentiation 36) is the gatekeeper of cardiac FA metabolism. Preferential localisation of CD36 to the sarcolemma is one of the initiating cellular responses in the development of muscle insulin resistance and in the type 2 diabetic heart. Post-translational S-acylation controls protein trafficking, and in this study we hypothesised that increased CD36 S-acylation may underpin the preferential sarcolemmal localisation of CD36, driving metabolic and contractile dysfunction in diabetes.
METHODS: Type 2 diabetes was induced in the rat using high fat diet and a low dose of streptozotocin. Forkhead box O1 (FoxO1) transcriptional regulation of zDHHC4 (zinc finger DHHC-type palmitoyltransferase 4) and subsequent S-acylation of CD36 was assessed using chromatin immunoprecipitation (ChIP) sequencing, ChIP-quantitative polymerase chain reaction, luciferase assays, siRNA (small interfering RNA) and shRNA silencing.
RESULTS: Type 2 diabetes increased cardiac CD36 S-acylation, CD36 sarcolemmal localisation, FA oxidation rates and triglyceride storage in the diabetic heart. CD36 S-acylation was increased in diabetic rats, db/db mice, diabetic pigs and insulin-resistant human iPSC-derived cardiomyocytes, demonstrating conservation between species. The enzyme responsible for S-acylating CD36, zDHHC4, was transcriptionally upregulated in the diabetic heart, and genetic silencing of zDHHC4 decreased CD36 S-acylation. We identified that zDHHC4 expression is under the regulation of the transcription factor FoxO1. Diabetic mice with cardiomyocyte-specific FoxO1 deletion had decreased cardiac zDHHC4 expression and decreased CD36 S-acylation, which was further confirmed using diabetic mice treated with the FoxO1 inhibitor AS1842856. Pharmacological inhibition of zDHHC enzymes in diabetic hearts decreased CD36 S-acylation, sarcolemmal CD36 content, FA oxidation rates and triglyceride storage, culminating in improved cardiac function in diabetes. Conversely, inhibiting the de-acylating enzymes in control hearts increased CD36 S-acylation, sarcolemmal CD36 content and FA metabolic rates in control hearts, recapitulating the metabolic phenotype seen in diabetic hearts.
CONCLUSIONS: Activation of the FoxO1-zDHHC4-CD36 S-acylation axis drives metabolic and contractile dysfunction in the type 2 diabetic heart.